Antecedents of global brands preference among generation Y in Malaysia - Abdul Talib, Asmat Nizam; Yusof, Mahjabin (IGI Global, 2020)
Consumers in Asia are known for preferring global brands as opposed to the locally manufactured ones. The emergence of global brands in the marketplace has brought many benefits as well as many obstacles, especially for local marketers. This study explored the antecedents of global brands preference among Gen-Y in Malaysia, notably country-of-origin, quality, design, and advertising. Three hundred students of higher learning institutions in Malaysia were selected to take part in the study. Multiple regression analysis was used to analyze the data. It was found that the country-of-origin, quality, and design positively influence global brands preference among Gen-Y. However, advertising was found to influence preferences negatively. The findings could help local marketers develop and execute their marketing plan better and global marketers to improve their strategies and be more competitive. Marketers should focus on the above aspects in their marketing plan to capture the markets of Gen-Y in Malaysia and thus addressing their needs and wants better.